(untitled) (Journal of Environmental Bioremediation and Toxicology, 2024)
Skin absorption continues to be a significant pathway for heavy metal toxicity in humans. This study investigated the concentrations of heavy metals (copper, iron, cadmium, arsenic, nickel, chromium, and lead) in locally produced and imported cosmetic products sold in Gombe Metropolis, Nigeria, using Atomic Absorption Spectrometry (AAS). Results indicated variable compliance with regulatory standards: certain metals exceeded permissible limits, while others remained within acceptable thresholds. For instance, Pb levels in Powder C1, Creams A1 and A2, Lotions B1 and B2, and Lipsticks D1 and D2 were below the 0.01 mg/kg limit. However, Arsenic (As) concentrations in Powders C1 and C2 (0.2964 mg/kg and 0.4725 mg/kg, respectively) surpassed the 0.05 mg/kg threshold. Similarly, Nickel (Ni) in these powders exceeded the 0.02 mg/kg limit, and Chromium (Cr) levels in Powder C2 (0.2981 mg/kg) and Cream A1 (0.1659 mg/kg) far exceeded the 0.05 mg/kg standard. Iron (Fe) remained within safe limits across all samples. Notably, locally manufactured cosmetics demonstrated greater adherence to permissible levels of heavy metals compared to imported products. Elevated concentrations of these metals in cosmetics pose health risks via dermal absorption or accidental ingestion, underscoring the need for stricter regulatory compliance by manufacturers to safeguard consumer health.